IMPLEMENTASI MANAJEMEN KELAS: SEBAGAI UPAYA MEMBANGUN EFEKTIVITAS PEMBELAJARAN - Al DARMONO (Inisiasi : Jurnal Manajemen Pendidikan Islam, 2022)
Class management is very important to be considered and carried out by the teacher in the learning activities carried out. Learning does not only prioritize the learning process, but class management must be carried out in creating effective learning. By creating a conducive and comfortable learning atmosphere, it can encourage students to learn more optimally. The purpose of this study 1) to know the concept of classroom management, 2) to know the scope of classroom management. This research uses qualitative methods, data collection techniques using library research. Methods of data collection is done by documentation techniques, and literature. The results of this study conceptually class management is class management or class management is an activity to regulate and organize within the scope of the class so that the learning process runs optimally. The scope of classroom management includes planning, implementing, monitoring, and evaluating.